Differences in Awareness of Chinese Dietary Guidelines Among Urban and Rural Residents: A Cross-Sectional Survey in Southwest China - Ke Jiang; Ke Jiang; Ke Jiang; Yaqi Wen; Yaqi Wen; Yaqi Wen; Shengping Li; Shengping Li; Shengping Li; Tiankun Wang; Tiankun Wang; Tiankun Wang; et al. (Frontiers Media S.A., 2023)
Objectives: This study aimed to compare the awareness of Chinese dietary guidelines (CDGs, 2016) between rural and urban areas in Southwest China and identify the factors that affect CDGs (2016) awareness.Methods: This cross-sectional survey included 8,320 individuals aged 18-75 years from Chongqing, Sichuan, Guizhou, and Yunnan, China. Convenience sampling method was adopted to select the survey subjects and face-to-face surveys in each region were conducted to collect data. Descriptive statistics and generalized linear model were used to evaluate differences in awareness of CDGs among urban and rural residents and its influencing factors.Results: Overall CDGs awareness was low in urban and rural areas, although the awareness rate was higher in the former than in the latter (29.1% vs. 19.9%, respectively). Region, education level, Body Mass Index (BMI), gender, income, and age are the influencing factors of CDGs awareness. Urban participants were likely to acquire relevant knowledge from social media, books/magazines, family/friends, and experts. However, rural participants were likely to acquire relevant knowledge from food sales staff (p < 0.05).Conclusion: Rural residents are less aware of CDGs than their urban counterparts in Southwest China. Future dietary education should adopt different strategies for different populations, with considerable focus on rural residents.